Cytologic alterations in the oral mucosa after chronic exposure to ethanol Alterações citológicas na mucosa bucal após exposição crônica ao etanol - Sílvia Regina de Almeida Reis; Alexandre Ribeiro do Espírito Santo; Miguel Gustavo Setúbal Andrade; Moysés Sadigursky (Brazilian Oral Research, 2006)
The effects of ethanol alone on the oral mucosa are still poorly understood, especially because there are few non-smoking chronic consumers of alcoholic beverages. The aim of this study was to evaluate the frequency of micronucleus, abnormal nucleus/cytoplasm ratio, pyknosis, karyorrhexis and karyolysis in exfoliated cells from the buccal mucosa and from the lateral border of the tongue in 36 non-smoker alcoholics (ethanol group) and 18 non-smokers and non-drinkers (control group). The Papanicolaou method was used. Since alcoholics generally have hepatobiliary involvement, the association between serum gamma-glutamyl transpeptidase (GGT) and some of the analyzed oral mucosa alterations was also investigated. The ethanol group showed a significant increase in the frequency of all alterations analyzed in the tongue cells when compared with the control group (p < 0.01; Mann-Whitney). However, the presence of these changes in buccal mucosa cells was not statistically significant (p > 0.05; Mann-Whitney). In the ethanol group, the correlation between serum GGT and the frequency of micronucleus and abnormal nucleus/cytoplasm ratio in oral mucosa cells was not significant (p > 0.05; Spearman). In conclusion, chronic exposure to ethanol may be associated with carcinogenic cytologic changes in the oral mucosa, even in the absence of tobacco smoking. These alterations were not correlated with hepatobiliary injury. Os efeitos do etanol isoladamente sobre a mucosa bucal permanecem pouco esclarecidos, sobretudo devido ao baixo número de não-fumantes consumidores crônicos de bebidas alcoólicas. O objetivo deste estudo foi avaliar as freqüências de micronúcleo, relação núcleo/citoplasma anormal, picnose, cariorrexe e cariólise em células esfoliadas da mucosa jugal e do bordo lateral da língua de 36 alcoólatras não-fumantes (grupo etanol) e 18 abstêmios de álcool e fumo (grupo controle). O método de Papanicolaou foi utilizado. Uma vez que indivíduos alcoólatras geralmente apresentam comprometimento hepatobiliar, a associação entre gama-glutamil transpeptidase (GGT) sérica e algumas das alterações citológicas analisadas também foi investigada. O grupo etanol mostrou um aumento significativo nas freqüências de todas as alterações investigadas nas células da língua quando comparado ao grupo controle (p < 0,01; Mann-Whitney). No entanto, a presença de tais mudanças na mucosa jugal não foi estatisticamente significante (p > 0,05; Mann-Whitney). No grupo etanol, a correlação entre GGT sérica e as freqüências de micronúcleo e a relação núcleo/citoplasma anormal em células da mucosa bucal não foi significativa (p > 0,05; Spearman). Conclui-se que o consumo crônico de etanol pode estar associado a alterações citológicas carcinogênicas na mucosa bucal, mesmo na ausência de exposição ao fumo. Tais alterações não apresentaram correlação com o comprometimento hepatobiliar.